Numerical and experimental investigation into the evolution of the shock wave when a muzzle jet impacts a constrained moving body - Zijie Li; Hao Wang; Changshun Chen; Kun Jiang (Defence Technology, 2024)
The gun-track launch system is a new special launch device that connects the track outside the muzzle. Because it is constrained by the track, the characteristics of development of the muzzle jet differ from those of the traditional muzzle jet. Specifically, it changes from freely developing to doing so in a constrained manner, where this results in an asymmetric direction of flow as well as spatio-temporal coupling-induced interference between various shock waves and the formation of vortices. In this background, the authors of this article formulate and consider the development and characteristics of evolution of the muzzle jet as it impacts a constrained moving body. We designed simulations to test the gun-track launch system, and established a numerical model based on the dynamic grid method to explore the development and characteristics of propagation of disturbances when the muzzle jet impacted a constrained moving body. We also considered models without a constrained track for the sake of comparison. The results showed that the muzzle jet assumed a circumferential asymmetric shape, and tended to develop in the area above the muzzle. Because the test platform was close to the ground, the muzzle jet was subjected to reflections from it that enhanced the development and evolution of various forms of shock waves and vortices in the muzzle jet to exacerbate its rate of distortion and asymmetric characteristics. This in turn led to significant differences in the changes in pressure at symmetric points that would otherwise have been identical. The results of a comparative analysis showed that the constrained track could hinder the influence of reflections from the ground on the muzzle jet to some extent, and could reduce the velocity of the shock waves inducing the motion of the muzzle as well as the Mach number of the moving body. The work here provides a theoretical basis and the requisite technical support for applications of the gun-track launch system. It also sheds light on the technical bottlenecks that need to be considered to recover high-value warheads.